Respuesta :

Answer:

[tex]y = -3x - 3[/tex]

Step-by-step explanation:

From the graph, we have the following coordinate points:

[tex](x_1,y_1) = (0,-3)[/tex]

[tex](x_2,y_2) = (-1,0)[/tex]

To determine the equation, we start by calculating the slope:

[tex]m = \frac{y_1 - y_2}{x_1 - x_2}[/tex]

This gives:

[tex]m = \frac{-3 - 0}{0 - (-1)}[/tex]

[tex]m = \frac{-3}{0+1}[/tex]

[tex]m = \frac{-3}{1}[/tex]

[tex]m = -3[/tex]

The equation is then calculated using:

[tex]y - y_1 = m(x - x_1)[/tex]

Where

[tex](x_1,y_1) = (0,-3)[/tex]

[tex]m = -3[/tex]

This gives:

[tex]y - (-3) = -3(x - 0)[/tex]

[tex]y - (-3) = -3(x)[/tex]

[tex]y +3 = -3(x)[/tex]

[tex]y +3 = -3x[/tex]

Make y the subject

[tex]y = -3x - 3[/tex]

ACCESS MORE